Selection of promising genotypes of faba bean (Vicia faba) by deciphering genetic variability and trait association - Vijaypal Singh Thakur; Yash Kumar Singh; Neha Thomas; VP Sahi (Current Horticulture, 2025)
Twenty-ﬁve genotypes of faba beans were evaluated for selection of promising genotypes by deciphering genetic variability and trait association. The experiment was conducted in a Randomized Block Design with three replications at Department of Genetics and Plant Breeding, Naini Agriculture Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Naini, Prayagraj during rabi season of 2023. The plant-to-plant distance was 20 cm and row-to-row distance of 30 cm. The data were recorded from randomly selected ﬁve plants for each genotypes for each replications for nineteen characters viz. days to ﬁrst ﬂowering; days to 50% ﬂowering; plant height (cm); number of branches/plant; number of nodes on main branch; number of ﬂowers/plant; leaﬂet length (cm); leaﬂet width (cm); days to pod initiation; number of pods/plant; pod length (cm); pod width (cm); days to maturity; number of seeds/pod; seed index (gm); harvest index (%); biological yield (gm); seed yield; seed yield/hectare (tonnes/ha). Analysis of variance showed signiﬁcant variation among diﬀerent genotypes for all characters studied. Moderate GCV and PCV was recorded for number of branches/plant, number of pods/plant, pod width, number of seeds/pod, seed index, biological yield and seed yield per hectare. High estimate of heritability coupled with high genetic advance as percent of mean and moderate GCV was recorded for number of branches/plant, number of pods/plant, pod width, number of seed/pod, seed index, biological yield and seed yield. This indicates closeness of respective σ2p and σ2g value thereby low environmental eﬀect on expression of these characters. Positive and signiﬁcant correlation were observed for number of branches/plant, number of nodes in main branch, number of ﬂowers/plant, number of pods/ plant, pod length, days to maturity, plant height, leaﬂet length, number of seeds/pod, biological yield, days to ﬁrst ﬂowering, seed index and seed yield with seed yield (per plant) at genotypic level. While rest of the characters showed non-signiﬁcant association with seed yield. Signiﬁcant positive association of these above attributes indicated that these attributes were mainly inﬂuencing the seed yield in faba bean.